2018
DOI: 10.1094/pdis-07-17-1069-re
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine red blotch virus: Absence in Swiss Vineyards and Analysis of Potential Detrimental Effect on Viticultural Performance

Abstract: Grapevine red blotch virus (GRBV) is a recently described virus that infects grapevine. Little information is available on the possible occurrence and distribution outside North America. Therefore, we surveyed commercial vineyards from the three major grape-growing regions in Switzerland to determine the presence or absence of GRBV. In total, 3,062 vines were analyzed by polymerase chain reaction. None of the vines tested positive for GRBV, suggesting the absence of GRBV from Swiss vineyards. We also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
3
28
0
2
Order By: Relevance
“…Furthermore, we could confirm the presence of the GRSPaV by way of its 28 kDa coat protein in GRBV-free and infected plants at similar expression levels, confirming RT-PCR results produced at Agroscope ( Reynard et al, 2018a ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, we could confirm the presence of the GRSPaV by way of its 28 kDa coat protein in GRBV-free and infected plants at similar expression levels, confirming RT-PCR results produced at Agroscope ( Reynard et al, 2018a ).…”
Section: Discussionsupporting
confidence: 83%
“…We could identify the V1 and V2 GRBV proteins in petioles of GRBV-infected plants but not in the leaves. V1 and V2 were the only GRBV proteins identified from the six possible open-reading frames of the GRBV genome as deposited in the NCBI GenBank database with accession number MF276895 ( Reynard et al, 2018a ). We achieved sequence coverages of 75.0% for the V1 (amino acid range of 33–324) and 53.8% for V2 (range 60–165) by combining the shotgun and in-gel results (Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no response of any of the vegetative growth variables to virus status in either year, with only a small effect of irrigation treatment on pruning mass in 2018-likely due to the larger differences in vine water status that year. Recently, Martıńez-Lüscher et al (2019) showed no GRBD effect on vine pruning mass in Cabernet Sauvignon, while Reynard et al (2018) reported pruning mass reductions of 33-35% in Gamay. Considering that leaf gas exchange was not reduced in GRBV+ vines preveraison in this study and in Martıńez-Lüscher et al (2019), and that most shoot elongation and canopy development occurs during this time (Matthews et al, 1987), it seems unlikely that GRBV infection would negatively impact vegetative growth unless there were other confounding biotic or abiotic factors.…”
Section: Short-term Responses Of Vine Growthmentioning
confidence: 99%